Quantificação e fracionamento da serapilheira em povoamentos clonais de Tectona grandis em diferentes idades - Costa, Jonathan Lucas Tyszka (2023)
Nutrient cycling is an important component for understanding forest ecosystems and improving their management with a view to increasing production and productivity, as there is little information about nutrient supply and recycling in Tectona grandis clonal plantations. And the litter as an important nutrient cycling factor was the main interest of the study. This study aimed to: (1) quantify litter incorporation, (2) nutrient concentration and accumulation, and (3) soil evaluation. The study was carried out in clonal stands of the species Tectona grandis Linn f., at different ages (3, 7 and 13 years) located in the municipality of Nova Maringá - MT. The collection of litter was through the implementation of three plots at each age, where each plot has a dimension of 7 m x 7 m (49 m² area). The litter was collected in bags and sent to the laboratory, where it was properly separated and weighed by each of its components (leaf, branch, seed and miscellaneous), and samples were taken in triplicate to determine the dry weight of the components. dried in ovens. Soil collection was carried out inside the litter plots, extracting samples in the layers of 00-05, 05-10, 10-15 cm, where they were carried out in duplicates, one in the row and the other in between the planting rows. For the data, analysis of variance (ANOVA) and the Tukey test were performed to verify differences between means. The analysis was carried out using the R software resources. The litter collected in the plots with thirteen, seven and three years of age were estimated, respectively, 8,881.17, 4,620.40 and 1,814.31 kg.ha. The branches represented around 53% of the total litter deposited, the leaves, 30%, and the miscellaneous, 15%. The levels of macronutrients in litter showed average concentrations of 11.42, 8.48, 9.23 g.kg-1 of N, 1.28; 0.63; 0.67 g.kg-1 of P; 1.28; 1.08; 1.27 g.kg-1 of K; 9.37, 7.45, 7.6 g.kg-1 Ca, 1.65; 1.18; 1.43 g.kg-1 Mg; 1.75; 1.13; 1.17 g.kg-1 of S, at three, seven and thirteen years, respectively. The highest amount of nutrients deposited by litter was higher for stands aged thirteen, followed by seven and three years old, with the order of contribution of macronutrients N > Ca > S > Mg > P = K; N > Ca > Mg > S > K > P and N > Ca > Mg > K > S > P, respectively. Soil analyzes took place in soil divisions in plantations with 3, 7 and 13 years of age, revealing differences, indicating an effect between age and depth. The evaluation of the clonal planting system of Tectona grandis at different ages demonstrates that the amount of litter produced leads to soil fertilization due to planting maintenance.